Scaling Propensity of Water New Predictive Parameters - van Raalte-Drewes, M. (IWA Publishing, 2004)
The commonly used Saturation Index calculated at 10°C (SI10) is not suitable for practical situations. New parameters have been developed for simple and rapid analysis of calcium carbonate precipitation (scaling) phenomena which occur during the heating of drinking water: TPCC90 (Theoretically Precipitable Calcium Carbonate at 90°C) SI90 (Saturation Index at 90°C) NI (Nucleation Index) PPCC (Practically Precipitable Calcium Carbonate) Both TPCC90 and SI90 describe the hydrodynamic driven force for the scaling reaction. The nucleation index indicates at what rate calcium carbonate precipitation is accelerated by nuclei present in the water. Finally, the PPCC is a measurement under practical conditions, determining the rate of scaling. The suitability of these parameters for predicting scaling was assessed and detailed results are presented in this publication.